The synthesis and cholinesterase inhibitory activities of solasodine analogues with seven-membered F ring - Kielczewska, Urszula; Jorda, Radek; Gonzalez, Gabriel; Morzycki, Jacek W; Ajani, Haresh; Svrčková, Katarína; Štěpánková, Šárka; Wojtkielewicz, Agnieszka (Elsevier Science, 2021)
Solasodine analogues containing a seven-membered F ring with a nitrogen atom placed at position 22a were prepared from diosgenin or tigogenin in a four-step synthesis comprising of the simultaneous opening of the F-ring and introduction of cyanide in position 22 alpha, activation of the 26-hydroxyl group as mesylate, nitrile reduction, and N-cyclization. Solasodine, six obtained 22a(N)-homo analogues, as well as four 26a-homosolasodine derivatives and their open-chain precursors (13 in total) were tested as potential inhibitors of acetyland butyryl-cholinesterases and showed activity at micromolar concentrations. The structure-activity relationship study revealed that activities against studied esterases are affected by the structure of E/F rings and the substitution pattern of ring A. The most potent compound 8 acted as non-competitive inhibitors and exerted IC50 = 8.51 mu M and 7.05 mu M for eeAChE and eqBChE, respectively. Molecular docking studies revealed the hydrogen bond interaction of 8 with S293 of AChE; further rings are stabilized via hydrophobic interaction (ring A) or interaction with Y341 and W286 (rings B and C). Biological experiments showed no neurotoxicity of differentiated SH-SY5Y cells. More importantly, results from neuroprotective assay based on glutamate-induced cytotoxicity revealed that most derivatives had the ability to increase the viability of differentiated SH-SY5Y cells in comparison to galantamine and lipoic acid assayed as standards. The newly synthesized solasodine analogues are able to inhibit and to bind cholinesterases in noncompetitive mode of inhibition and exhibited neuroprotection potential of differentiated neuroblastoma cells after Glu-induced toxicity.
Syntéza a cholinesterázová inhibiční aktivita analogů solasodinu se sedmičlenným F kruhem
Keywords: ring expansion; solasodine; spiro compounds; spirostane; steroidal alkaloids; cholinesterase inhibition; rozšíření prstenu; solasodin; spiro sloučeniny; spirostan; steroidní alkaloidy; inhibice cholinesterázy